(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores the fundamental role of practical training in the development of professional competencies among future educators. While theoretical knowledge provides the foundation for teaching, it is the practical application within real classroom environments that fosters the necessary skills for effective instruction, classroom management, and psychological adaptation. The study analyzes the integration of theory and practice, highlighting how pedagogical internships bridge the gap between academic learning and professional reality. The findings suggest that a structured, reflective, and continuous practical approach is essential for producing high-quality pedagogical personnel capable of meeting modern educational challenges.